Lixisenatide in type 1 diabetes: A randomised control trial of the effect of lixisenatide on post‐meal glucose excursions and glucagon in type 1 diabetes patients - Chitrabhanu Ballav; Archana Dhere; Irene Kennedy; Olorunsola F. Agbaje; Sarah White; Rachel Franklin; Bolette Hartmann; Jens J. Holst; Rury R. Holman; Katharine R. Owen (Endocrinology, Diabetes & Metabolism, 2020)
Abstract Aims The GLP1 agonist lixisenatide is glucagonostatic and reduces post‐prandial blood glucose (PPBG) in type 2 diabetes. This study investigates its impact in type 1 diabetes (T1D). Methods In a blinded, crossover trial, 25 patients with T1D were randomised to 4 weeks adjunctive treatment with lixisenatide (L) or placebo (P), with a 4‐week washout period. The primary outcome was percentage of 3 hours PPBG in target (4‐10 mmol/L) assessed by CGM before and after treatment. Participants also underwent post‐treatment standardised mixed meal test (MMT, n = 25) and hyperinsulinaemic hypoglycaemic clamp (n = 15). Results PPBG CGM readings in target were similar between L vs P (Mean % ± SE, breakfast 45.4 ± 6.0 vs 44.3 ± 6.0, P = .48, lunch 45.5 ± 5.8 vs 50.6 ± 5.3, P = .27 and dinner 43.0 ± 6.7 vs 47.7 ± 5.6, P = .30). HbA1C was similar between L vs P (64.7 ± 1.6 vs 64.1 ± 1.6 mmol/mol, P = .30). Prandial insulin fell after lixisenatide (dose change −0.7 ± 0.6 vs +2.4 ± 0.7 units/d, P = .004), but basal insulin dose was similar between groups. The post‐MMT glucose area under the curve (AUC) was lower with L than P (392.0 ± 167.7 vs 628.1 ± 132.5 mmol/L × min, P < .001), as was the corresponding glucagon AUC (140.0 ± 110.0 vs 304.2 ± 148.2 nmol/L × min, P < .001). Glucagon and counter‐regulatory hormone values at a blood glucose of 2.4 mmol/L during the hypoglycaemic clamp were similar between L and P. Conclusion In T1D, PPBG values were not altered by adjunctive lixisenatide although prandial insulin dose fell. Glucose and glucagon level during an MMT were significantly lower after lixisenatide, without affecting counter‐regulatory response during hypoglycaemia.